Uveitis Induced by Biological Agents Used in Cancer Therapy. (17th November 2021) - Deitch-Harel, Iris; Raskin, Eyal; Habot-Wilner, Zohar; Friling, Ronit; Amer, Radgonde; Kramer, Michal
ABSTRACT: Purpose : To report cases of uveitis induced by biological therapy given for cancer. Methods : Retrospective review of medical charts of patients. Results : Included were six patients aged 14–81 years. Three were treated with vemurafenib and one each with nivolumab, ipilimumab, and osimertinib. The oncological diagnoses were metastatic thyroid carcinoma, pleomorphic xanthoastrocytoma, metastatic melanoma, adenocarcinoma of the lung, and metastatic breast cancer. Ocular manifestations appeared 4–82 weeks after the biological treatment was initiated. The most common ocular presentation was anterior uveitis. Onset was sudden in all cases. The median duration of uveitis was 70 weeks. Treatment included topical or systemic corticosteroids; one patient received a single intravitreal steroid injection in one eye. Conclusions : Uveitis may rarely be induced by treatment with biological agents for cancer. Both oncologists and ophthalmologists should be aware of this potential side effect. Early detection and management can prevent permanent complications and save the patient's vision.